Combating Water Scarcity in Southern Africa Case Studies from Namibia - Msangi, Josephine Phillip; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This book offers a close examination of water scarcity as a developmental challenge facing member nations of the Southern African Development Community (SADC), the interventions that have been implemented to combat the situation and the challenges still outstanding. The first chapter paints the backdrop of the water scarcity problem, reviewing historical approaches from the 1992 Earth Summit in Rio de Janeiro to the Johannesburg World Summit on Sustainable Development (2002) to the United Nations Rio+20 Conference on Sustainable Development (2012), and recapping principles and agreements reached during and after these conferences. Chapter two examines the Southern Africa region$1 (Bs efforts to combat water scarcity including principles, policies and strategies and the responsibility of each member to implement them. Written by the editor, J.P. Msangi, the chapter describes Namibia$1 (Bs efforts to ensure management of scarce water. Beyond enacting management and pollution control regulations and raising public awareness, Namibia encourages research to ensure attainment of the requirements of both the SADC Protocol and its own water scarcity management laws. The next three chapters offer Namibia-based case studies on impacts of pollution on water treatment; on the effects of anthropogenic activities on water quality and on the effects of water transfers from dams upstream of Von Bach dam. The final chapter provides detailed summaries of the issues discussed in the book, highlighting conclusions and offering recommendations. Combating Water Scarcity in Southern Africa synthesizes issues pertinent to the SADC countries as well as to other regions, and offers research that up to now has not been conducted in Namibia.s
Chapter 1: General Introduction -- Chapter 2: Managing Water Scarcity in Southern Africa: Policy and Strategies -- Chapter 3: Trends and Impacts of Pollution on Water Treatment: The Case of Calueque-Oshakati Canal North-central Namibia -- Chapter 4: Monitoring the Effects of Anthropogenic Activities on Water Quality: Von Bach Dam, Namibia -- Chapter 5: The Effects of Water Transfers from Swakoppoort and Omatako Dams on Water Quality of Von Bach Dam, Namibia -- Chapter 6: Conclusions and Recommendations -- Index.
Keywords: Environmental sciences; Science (General).; Geography; Medicine; Environment; Environment, general; Science, general; Geography (general).; Medicine/Public Health, general; Earth Sciences, general; Environmental Monitoring/Analysis.